2017
DOI: 10.1111/jpn.12828
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre alleviates hepatic fat deposition via inhibiting lipogenic gene expression in meat ducks

Abstract: This study investigated the effect of dietary fibre (DF) supplementation on hepatic fat deposition of Cherry Valley meat ducks. A total of 600 1-d-old ducks were randomly allotted to five dietary fibre diets (1.46 (basal diet), 3.09, 4.15, 6.18 and 7.52% (analysed)) for 14 days. Growth performance decreased with increasing DF concentrations, when the DF level more than 6.18% the average daily gain (ADG) and feed conversion ratio (F/G) markedly decreased in meat ducks. Meat ducks supplemented over 4.15% DF had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
2
5
1
Order By: Relevance
“…Similarly, Huang et al [45] reported that soy lecithin upregulated the gene expression of FAS, acetyl-CoA carboxylase (ACC), and sterol regulatory element binding protein-1 (SREBP-1) in broilers. This is inconsistent with Qin et al [41], who found downregulation of expression of the previously mentioned gene in the liver with increasing DF% in meat ducks' diet, and an increase of the adipose triglyceride lipase. Furthermore, Hosseini et al [18] reported that dietary supplementation of lysolecithin or/and xylanase did not have any effect on hepatic lipogenic gene expression (FAS and L-FABP) of broiler chickens fed on a low energy diet.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Similarly, Huang et al [45] reported that soy lecithin upregulated the gene expression of FAS, acetyl-CoA carboxylase (ACC), and sterol regulatory element binding protein-1 (SREBP-1) in broilers. This is inconsistent with Qin et al [41], who found downregulation of expression of the previously mentioned gene in the liver with increasing DF% in meat ducks' diet, and an increase of the adipose triglyceride lipase. Furthermore, Hosseini et al [18] reported that dietary supplementation of lysolecithin or/and xylanase did not have any effect on hepatic lipogenic gene expression (FAS and L-FABP) of broiler chickens fed on a low energy diet.…”
Section: Discussioncontrasting
confidence: 79%
“…The obtained findings are in line with Beshara et al [31], who found that HDL was slightly higher, with lower TG level for ducks fed different levels of CF. Qin, et al [41], however, stated that higher DF% decreased serum TC and had no significant effect TG, HDL or LDL concentrations in growing ducklings. DF reduced serum LDL and increased HDL [42,43] as fiber interferes with lipid absorption and metabolism through binding to bile acid and cholesterol, consequently lowering serum lipids [44].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The RNA isolation and real-time polymerase chain reaction (PCR) were performed as previously described in our laboratory [18]. Briefly, total RNA was isolated from the duodenal and jejunal mucosa by using a TRIZOL reagent (Invitrogen, Carlsbad, CA, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Likes other avian species, dietary fiber was also beneficial to duck growth and gut health and ducks could adapt to a wide dietary crude fiber range from 3.09 to 7.52% ( Han et al, 2017 ). Furthermore, ducks fed with high dietary crude fiber levels had increased gizzard development, jejunal morphology, energy retention, excreta nutrients availability, and standardized ileal digestibility of amino acids, and high dietary fiber also alleviated hepatic fat deposition via inhibiting lipogenic gene expression in meat ducks ( Han et al, 2017 ; Qin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%